Pelaksanaan portfolio kerja kursus kajian rekaan seni visual di sekolah menengah (IR) - Norazmyra Yahya (2011)
The study was carried out to get clear insights on the completion of students portfolios, the extent of assistance given to the students and factors that influenced the students in completing the portfolios. It involved the Form Five students in a secondary school in Hilir Perak, Perak. The study used the qualitative method of an intrinsic case study. There were four students and a teacher adviser selected for the study. Data were collected using observations, interviews and document analysis. Observations were conducted on the Art Room and schools sorrounding area. Document analysis was based on the Guide Book for the Implementation and Evaluation of the Coursework for Visual Art Education and students portfolios. Data from the interviews were transcribed manually and analysed using content analysis method. Results showed that guidelines from the Malaysian Examinations Syndicate were followed by the teacher in the completion of the students portfolios. These included supervising, guiding, observing and continually recording students progress. Results also indicated that students did get assistance from their teacher adviser, peers and the school. The study also found that the teacher adviser, school, families, financial, self readiness and time were the factors that influenced the students in completing their portfolios. It was concluded that the coursework portfolio implementation for the Visual Art Education subject required commitment from the teacher adviser. Assistances received by the students and the influencing factors also required proper considerations in ensuring the portfolio completion process was well implemented. The suggestions made were to conduct in-house courses for teacher advisers, A Peer Group Day, training module, colouring workshop, Nano Achievement classes and Art Camp.